An Investigation into The Effect of Social Media on Body Image and Self-Esteem on British Women Aged 20-23 - Jackson, Madeline (2022)
The purpose of this study is to examine the effects of social media on body image and self-esteem for British women aged 20-23. Literature on this topic has examined the effects of social media on body image and the effects of social media on self-esteem separately. Literature proving the negative effects of social media has mainly applied to Facebook – which is not often used by this demographic, hence the need for this study. The four main themes found in this study are; social media is damaging to vulnerable people, a bad aspect of social media is comparison, there is a need for a real and non- perfect life to be shown and the body positive movement and societal change go hand in hand. This study finds that the parts of social media that effect self-esteem and body image the most are; the fact that its image based, comparison with people similar to them and their previous self, the fact that perfect lives and people are portrayed and the editing of images. The effects of social media can be reduced by; showing real life on social media and by posting content that follow the body positive movement’s ideals. Therefore, this study shows practical ways that individuals and managers can help to reduce the negative effects of social media on body image and self-esteem. Finally, the body positive trend was found to have a positive impact on the self-esteem and body image of this demographic. And it was discovered that content that follows the ideas of the body positive movement and societal change and both needed to prevent the negative effects of social media.